Nupr1 mediates renal fibrosis via activating fibroblast and promoting epithelial‐mesenchymal transition. Issue 3 (22nd February 2021) - Zhou, Ruimei; Liao, Jiashun; Cai, Dunpeng; Tian, Qin; Huang, Enping; Lü, Tianming; Chen, Shi‐You; Xie, Wei‐Bing
Abstract: Renal interstitial fibrosis (RIF) is a pathological process that fibrotic components are excessively deposited in the renal interstitial space due to kidney injury, resulting in impaired renal function and chronic kidney disease. The molecular mechanisms controlling renal fibrosis are not fully understood. In this present study, we identified Nuclear protein 1 (Nupr1), a transcription factor also called p8, as a novel regulator promoting renal fibrosis. Unilateral ureteral obstruction (UUO) time‐dependently induced Nupr1 mRNA and protein expression in mouse kidneys while causing renal damage and fibrosis. Nupr1 deficiency ( Nupr1 −/− ) attenuated the renal tubule dilatation, tubular epithelial cell atrophy, and interstitial collagen accumulation caused by UUO. Consistently, Nupr1 −/− significantly decreased the expression of type I collagen, myofibroblast markers smooth muscle α‐actin (α‐SMA), fibroblast‐specific protein 1 (FSP‐1), and vimentin in mouse kidney that were upregulated by UUO. These results suggest that Nupr1 protein was essential for fibroblast activation and/or epithelial‐mesenchymal transition (EMT) during renal fibrogenesis. Indeed, Nupr1 was indispensable for TGF‐β‐induced myofibroblast activation of kidney interstitial NRK‐49F fibroblasts, multipotent mesenchymal C3H10T1/2 cells, and the EMT of kidney epithelial NRK‐52E cells. It appears that Nupr1 mediated TGF‐β‐induced α‐SMA expression and collagen synthesis by initiating Smad3 signaling pathway. Importantly, trifluoperazine (TFP), a Nupr1 inhibitor, alleviated UUO‐induced renal fibrosis. Taken together, our results demonstrate that Nupr1 promotes renal fibrosis by activating myofibroblast transformation from both fibroblasts and tubular epithelial cells.